Does Transfer Pricing Costs and Profitability Impact Tax Avoidance? - Gabriel Anderson; Marthinus Ismail (Jurnal Akuntansi, 2023)
This study is examined with the target information whether there is an impact arising from transfer pricing and returns on assets to tax avoidance. This study uses secondary data that has been collected from the Indonesia Stock Exchange (IDX) in the form of financial reports (annual) for 2019-2021 in the trade, services & investment sector. The sample selection used a purposive sampling method. The results obtained from tests carried out on companies in the trade, service & investment sector, namely, transfer pricing has an impact on the possibility of carrying out tax avoidance with a value of 0.00, return on assets (ROA) has no impact on tax avoidance with a value of 0.053, and transfer pricing and return on assets (ROA) as a distinctive effect on tax avoidance with a value of 0.00. Keywords: Transfer Pricing, Return on Assets, and Tax Avoidance